BUDGETARY PARTICIPATION, INFORMATION ASYMMETRY, AND BUDGET IN LOCAL GOVERNMENT: EVIDENCE FROM TEBO REGENCY - Sanjaya, Pebi; Mansur, Fitrini; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2026)
This study examines the effects of budget participation and information asymmetry on budget slack at the Tebo Regency Manpower and Transmigration Office. Budget slack occurs when employees intentionally underestimate revenue or overestimate expenditures, reducing the efficiency and accountability of public financial management. A quantitative approach with an associative research design was employed. The study involved all 30 employees responsible for budget preparation, using a saturated sampling (census) technique. Data were collected through structured questionnaires and analyzed using Partial Least Squares (PLS). The findings indicate that budget participation has a positive and significant effect on budget slack, suggesting that greater employee involvement in budgeting may increase the likelihood of creating slack. Information asymmetry also has a positive and significant effect, indicating that unequal access to information between subordinates and supervisors encourages budget slack. Furthermore, budget participation and information asymmetry jointly have a significant influence on budget slack. These results highlight the importance of improving transparency, communication, and internal control to minimize budget slack and enhance accountability and effectiveness in public sector financial management.